(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. This thesis explores the concept of sociolinguistic competence and its impact on the speaking performance of students in foreign language education. It defines sociolinguistic competence as the ability to use language appropriately in various social contexts, incorporating elements such as cultural norms, speech acts, and register variations. The study employs a mixed-methods approach, combining quantitative assessments of students’ speaking performances with qualitative interviews to gain insights into their understanding of sociolinguistic norms, that emphasize the importance of teaching not only linguistic accuracy but also sociolinguistic awareness to foster effective communication in diverse settings.